Up in smoke: considerations for lithium-ion batteries in disposable e-cigarettes - Reid, HT; Fordham, A; Rasha, L; Buckwell, M; Brett, DJL; Jervis, R; Shearing, PR (Cell Press, 2023)
In recent years, the use of disposable electric (e)-cigarettes containing lithium-ion batteries in the UK has led to remarkable wastage, the full environmental impact of which is yet to be realized. This study investigates the suitability for reuse and safety aspects of cells found in disposable e-cigarettes. Through electrochemical and safety characterization techniques, the cells’ performance and hazards were evaluated. Rate capability and long-term cycling experiments showed that cells sold as disposable were capable of completing 474 cycles at 1C charge/discharge before reaching 80% capacity fade. A nail penetration test revealed significant gas expulsion and a maximum temperature of 495°C. However, the cell format prevented significant material ejection. This work outlines the potential health hazards and highlights the possibility for second-life use of disposable e-cigarette cells, shedding light on the environmental impact and safety considerations.